Loneliness Coping Strategies Training for College Student - Mega, Tiolin; Salsabila, Nurrahmah; Yurni, Yurni; Nurhusna, Nurhusna (Jurnal Pengabdian Masyarakat Jurusan Keperawatan, 2023)
This community service activity is carried out with the aim of providing students with an understanding of coping strategies to overcome the equality problems they face. A total of 12 first year students were given training and through Focus group discussion activities, they were asked to discuss their feelings of loneliness and appropriate coping strategies to overcome them. The results of this training show changes in students' attitudes and behavior, students view the equality problems they face more positively and they are able to choose the right coping strategy.